EFFECT OF CALCIUM PIDOLATE SUPPLEMENTATION THROUGH DRINKING WATER ON EGG SHELL QUALITY - M. A., Wirya; Umiarti, A. T.; Wirapartha, M. (Jurnal Peternakan Tropika, 2024)
This study aimed to determine the benefits of calcium pidolate supplementation through drinking water on egg quality of 70-week-old Isa Brown hens. The research was conducted at Sari Mulya chicken farm located in Tunjuk Village, Tabanan District, Bali and lasted for four weeks. Using a completely randomized design consisting of three treatments and six replications. Each replicate contained 5 chickens. There were 90 chickens used in this study. The three treatments consisted of P0 (chicken given drinking water without additional calcium pidolate supplement), P1 (chicken given drinking water mixed with 0.3g calcium pidolate supplement) and P2 (chicken given drinking water mixed with 0.5g calcium pidolate supplement). The observed variables were egg shell weight, egg shell thickness, egg damage percentage and Hen Day Production (HDP). The results showed that shell weight, shell thickness, and egg damage in treatments P1 and P2 had significant results (P<0.05). HDP in P1 and P2 treatments did not affect the results (P>0.05) and produced the same percentage of hen day production as P0. The conclusion of this study is that the provision of 0.3 g and 0.5 grams of calcium pidolate supplements can increase the weight of the shell, the thickness of the shell and reduce the percentage of egg damage and produce the same Hen Day Production as the control treatment.